The body in therapy: experiences of Sensorimotor Psychotherapy - Dinas, Sharonjit (2012)
Background: Sensorimotor Psychotherapy is an approach for working with people who have experienced trauma (e.g. post-traumatic stress disorder [PTSD]) that is based on contemporary philosophies of embodiment and the expanse of neurobiological evidence for the effect of psychological trauma on the physical body. Thus, Sensorimotor Psychotherapy places central importance on working with the body in therapy.